Shin'iseihaito (Xinyiqingfeitang) Suppresses the Biofilm Formation of Streptococcus pneumoniae In Vitro. (16th April 2017) - Minami, Masaaki; Konishi, Toru; Takase, Hiroshi; Makino, Toshiaki
Abstract : Streptococcus pneumoniae ( S. pneumoniae ) is the important pathogen that causes otolaryngeal diseases such as sinusitis. S. pneumoniae frequently forms the biofilm to prevent severe circumstances such as antimicrobial agents. Shin'iseihaito (xinyiqingfeitang) is a formula of Japanese traditional Kampo medicine that has 9 crude drugs and provides the medicinal usage for sinusitis. The objective of the present study is to reveal the mechanism of antibiofilm activity by Shin'iseihaito extract (SSHT). SSHT significantly inhibited the formation of biofilm from S. pneumoniae ATCC 49619 in dose- and time-dependent manners. SSHT also significantly suppressed the biofilm formation by other five different cps types of S. pneumoniae clinical isolates. We found that the extracts of 8 out of 9 components in Shin'iseihaito had the inhibitory effects of biofilm formation, and the extract of the root of Scutellaria baicalensis had the strongest effect among the ingredients of Shin'iseihaito. We found that the capsule of SSHT-treated S. pneumoniae was significantly thinner than that of the untreated group and that SSHT reduced the hydrophobicity of bacterial cell surface. Our results suggest that Shin'iseihaito may be a useful agent for the treatment of S. pneumoniae -induced sinusitis because of the inhibition of biofilm formation of S. pneumoniae .